Change of Staphylococcus Aureus and Salmonella During Storage Period of Food Wastes in China - Panyue Zhang; Hao Wu; Fan Li; Juan Li; Gaopeng Li; Jianhua Wang (The Global Environmental Engineers, 2015)
ood wastes, such as animal feedstuff, may result in risks of disease spreading. Changes of Staphylococcus aureus and Salmonella in the food wastes during storage period were investigated in this paper. Staphylococcus aureus were tested by plate count and coagulase test, and Salmonella were tested by plate count and PCR assay. Results showed that both Staphylococcus aureus and Salmonella existed in the food wastes. After 48 h storage at 20 oC and 37 oC, the amount of Staphylococcus aureus decreased from 103 - 105 CFU/g to 102 and 0 CFU/g respectively. The amount of Salmonella decreased from 5.5x106 - 4.6x107 CFU/g to a range between 2.0x104 and 2.0x105 CFU/g after 48 h storage at 20 oC, and it was less than 20 CFU/g after 48 h storage at 37 oC. The two pathogenic bacteria would be restricted by pH decrease, which was caused by the fermentation of the food wastes.